Zero‐Dimensional Organic Copper(I) Iodide Hybrid with High Anti‐Water Stability for Blue‐Light‐Excitable Solid‐State Lighting. Issue 12 (21st April 2022) - Su, Binbin; Jin, Jiance; Peng, Yinhui; Molokeev, Maxim S.; Yang, Xiaobao; Xia, Zhiguo
Abstract: The discovery of rare‐earth free luminescent materials with blue‐light‐excitable characteristic is of great importance for solid‐sate lighting applications. Herein, a Cu(I)‐based 0D luminescent hybrid ( 1, 3‐dppH2 )2 Cu4 I8 ∙H2 O is synthesized by a facile solution method, and it shows the orange‐red emission peaking at 625 nm upon 460 nm excitation. The structure‐related luminescence mechanism has been elaborated by experimental and theoretical investigations. Moreover, the emission intensity remains unchanged even after continuous water treatment for 60 days due to the improved structural stability originating from intermolecular π–π interaction between organic cations. A warm white light‐emitting diode (LED) device with the color rendering index of 91.4% has been fabricated by combining the 440 nm LED chip, green‐emitting Lu3 Al5 O12 :Ce 3+, and ( 1, 3‐dppH2 )2 Cu4 I8 ∙H2 O. This work provides a new design route towards 0D cuprous halide materials and will initiate more exploration of their intrinsic luminescence mechanism. Abstract : A 0D organic copper(I) iodide hybrid, ( 1, 3‐dppH2 )2 Cu4 I8 ∙H2 O, demonstrates a broadband orange‐red emission peaking at 625 nm, with a full‐width at half‐maximum (FWHM) of 180 nm under 460 nm excitation, and it also exhibits an excellent anti‐water stability. The blue‐light‐excitable characteristic and excellent moisture stability make these organic copper(I) iodide clusters highly suitable for solid‐state lighting application.